Assessment of Integrated Plant Nutrient Management in Tomato through Farmers Participatory Approach - S.K. Pandey , G.D. Nigam , R.P. Singh , A.P.Dwivedi; S.R.K. Singh (Indian Journal of Extension Education, 2013)
Tomato (Lycopersicon esculentum Mill.) is one of the most remunerative and important vegetable crop widely grown and consumed in India. Injudicious use of fertilizers for higher yield in tomato is very common among farming communities which not only causes reduction of total yield gradually, but also is one of the major factors for higher incidence of biotic and abiotic stresses in commercial production. The farmers participatory trials were conducted by Krishi Vigyan Kendra, Chandauli district of Uttar Pradesh at farmers fields in two villages to assess the technological gap in tomato production and to evaluate IPNM technology for its effectiveness during Rabi 2008 and Kharif 2009. Eight technological gaps including application of fertilizer and pesticide for commercial tomato production were identified. The package of IPNM includes application of 10 tonnes FYM/ha + 150:80:60 kg NPK/ha + root dip of seedling in Azotobactor solution before transplanting + foliar spray of ferrous ammonium sulphate @ 20 ppm at 30, 45 and 75 days after transplanting. Findings of study revealed that maximum marketable fruit yield of 1025 qts/ha in Kharif 2009 and 955 qts/ha in Rabi 2008 were obtained from IPNM plots and 38.51 and 33.94 per cent increase in yield were recorded over farmers practice in respective seasons. The per cent loss of yield from total production due to diseased and inferior quality fruits were observed to be just double (8%) as compared with IPNM plot (4-5%). Partial budget analysis revealed that the net returns obtained from IPNM plot in Rabi 2008 and Kharif 2009 were higher i.e. ` 2,19,010 and ` 2,34,614 respectively than the farmers practice (` 1,42,240 and ` 1,43,235) in respective season. Reduction in cost of cultivation of ` 4,170 to ` 5,879 were also reported in IPNM plot in comparison with farmers practice . B:C ratio were found i.e., maximum 4.25 in Rabi 2008 and 4.23 in Kharif 2009 respectively in IPNM plot whereas in farmers practices it was 2.98 and 2.82 in respective seasons.